PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PEMBELAJARAN ILMU FALAK - Fahmi Fatwa Rosyadi Satria Hamdani (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2016)
Abstract: The Total Solar Eclipse (GMT) on March 9, 2016 coincides with the commemoration of Nyepi-Day of Silence, New Year of Caka 1938 in Bali. For Muslims who live in the area through the eclipse’s tracking are recommended to pray eclipse praying as it has been taught by the Prophet Muhammad SAW. However, Muslims who are in Bali included in the category of a minority, as most Balinese are Hindus. Hindus themselves will carry out various ceremonies to celebrate the New Year of Caka 1938. The research object of this article is to find out how Muslims in Bali take eclipse praying, while the major population there, Hindus, commemorate Barata Nyei on the same day. Furthermore, the implementation needs to use an effective way of learning about the GMT to face these issues. This study uses normative juridical sociological approach, in which the source used is taken based on the arguments contained in the Qur'an and the Hadith, the results of direct observation in the field, as well as cultural values prevailing in Bali. Those all are then combined in contextual learning model CTL. The study concludes that the tolerance between religious communities in Bali provides a positive learning about the importance of mutual respect of each community worshiping without interfering each other. The effective and practical learning that can be applied to the society is to select the main points of discussion of relevant and contextual, through a direct observation, and assistive devices that support it.Keywords; CTL, Eclipse, Nyepi, Muslims, Hindus.